Enteral nutrition in older adults with dementia in palliative care - Cicarelli, Paula Abrantes (2021)
The number of older adults and, consequently, the incidence of chronic non-communicable diseases, including dementia, have increased exponentially. Dementia leads to progressive loss of functionality, including food-related complications. This article presents results of an integrative review on the current scientific evidence of enteral nutritional therapy in patients with dementia in palliative care. Articles published between 2009 and 2019 were included. Data were collected in November 2019 in five databases, based on the following search words: “enteral nutrition”, “palliative care” and “dementia”. After applying the inclusion criteria, 11 articles remained in the sample. The main findings of these publications were divided into three categories: “palliative care and care plan”, “palliative care and enteral nutrition” and “enteral nutrition in older adults with dementia”. The results call attention to the need for decision making to be based on scientific evidence.